Understanding fundamentals and reaction mechanisms of electrode materials for Na‐ion batteries - Yu, Linghui (2020)
Development of efficient, affordable, and sustainable energy storage technologies has become an area of interest due to the worsening environmental issues and rising technological dependence on Li-ion batteries. Na-ion batteries (NIBs) have been receiving intensive research efforts during the last few years. Owing to their potentially low cost and relatively high energy density, NIBs are promising energy storage devices, especially for stationary applications. A fundamental understanding of electrode properties during electrochemical reactions is important for the development of low cost, high-energy density, and long shelf life NIBs. This Review aims to summarize and discuss reaction mechanisms of the major types of NIB electrode materials reported. By appreciating how the material works and the fundamental flaws it possesses, it is hoped that this Review will assist readers in coming up with innovative solutions for designing better materials for NIBs.